2021
DOI: 10.3390/chemosensors9120341
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2) As a Novel Biorecognition Element in A Cell-Based Biosensor for the Ultra-Rapid, Ultra-Sensitive Detection of the SARS-CoV-2 S1 Spike Protein Antigen

Abstract: Antigen screening for the SARS-CoV-2 S1 spike protein is among the most promising tools for the mass monitoring of asymptomatic carriers of the virus, especially in limited resource environments. Herewith, we report on the possible use of the angiotensin-converting enzyme 2 (ACE2), the natural receptor and entry point of the virus, as a biorecognition element for the detection of the S1 antigen combined with an established bioelectric biosensor based on membrane-engineered cells. The working principle of our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…At higher concentrations, the signals reach a plateau and start to decline. This phenomenon has been previously observed in several assays regarding the bioelectrical identification of molecules through membrane engineering [13,20,21]. It could be attributed to the saturation of the system when the concentration of the analyte exceeds a certain concentration.…”
Section: Optimizaton Of Membrane-engineered Sk-n-sh-s1 Protein Cells ...supporting
confidence: 54%
See 1 more Smart Citation
“…At higher concentrations, the signals reach a plateau and start to decline. This phenomenon has been previously observed in several assays regarding the bioelectrical identification of molecules through membrane engineering [13,20,21]. It could be attributed to the saturation of the system when the concentration of the analyte exceeds a certain concentration.…”
Section: Optimizaton Of Membrane-engineered Sk-n-sh-s1 Protein Cells ...supporting
confidence: 54%
“…The working principle of the assay is based on the already established technology of molecular identification through membrane engineering, according to which mammalian cells engineered by electroinserting membrane-bound biorecognition elements respond to the binding of the respective corresponding analytes with a very specific and measurable change in their membrane potential [11]. This approach has been recently used for the detection of the SARS-CoV-2 S1 protein in both laboratory and clinical settings using either anti-S1 antibodies [12] or the angiotensin-converting enzyme 2 (ACE2) [13] as the membrane-bound biorecognition elements. In two independent, subsequent clinical trials, the application of this novel bioelectric biosensor approach confirmed the detection of the virus in positive samples with a 92.8% success rate compared to RT-PCR [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 is used for ultra-fast and ultra-sensitive detection of SARS-CoV-2 as a novel biometric element in cell biosensor [ 95 ]. The results of various sensors indicate the potential of viral receptor ACE2 as a recognition element for screening variation in biosensors.…”
Section: Ace2-based Biosensors For Sars-cov-2 Detectionmentioning
confidence: 99%
“…The S-protein is the target for antibodies and can be an ideal viral recognition element for direct onsite detection of the SARS-CoV-2 . However, most of the S-protein detection methods or sensors have relied on the use of antibodies or ACE-2 enzymes as biorecognition elements, which require animal models and a longer time for synthesis, thereby making the design of assays very expensive, and also these proteins undergo irreversible denaturation at high temperatures and pH changes …”
Section: Introductionmentioning
confidence: 99%